Assessing sister chromatid exchanges in human peripheral lymphocytes exposed to tetrachlorvinphos during G0 phase - Akgun, Ebral; Hayal, Cobanoglu (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
While pesticides undeniably contribute to enhancing agricultural productivity, the escalating trend in their usage has given rise to a myriad of environmental and public health challenges over time. Tetrachlorvinphos, an organophosphate pesticide deemed potentially carcinogenic by the International Agency for Research on Cancer, is commonly employed to combat flies, mites, and larvae in animals, safeguarding public health in open spaces, and managing pest issues in domestic animals. We aimed to investigate the genotoxic and cytostatic effects of tetrachlorvinphos on human lymphocytes in the G0 phase of the cell cycle using the sister chromatid exchange (SCE) assay. We found that tetrachlorvinphos increased SCE values at 3 concentrations (5, 25, 50 μM). On the other hand, the increase in SCE values was found to be statistically significant only at the highest concentration (50 μM, p
Keywords: pesticides; organophosphates; genotoxic effects; cytostatic effects; sister chromatid exchange assay; G0 phase